POSTPARTUM NURSING CONSULTATIONS: PREVENTION OF BREAST COMPLICATIONS - Suellen Vienscoski Skupien; Ana Paula Xavier Ravelli; Laura Vargas Acauan (Universidade Federal do Paraná, 2016)
The present study aimed to identify breast disorders of postpartum women admitted to a maternity ward at a teaching hospital in the city of Ponta Grossa, Paraná. Quantitative exploratory study based on data collection performed from March to November 2015. The results obtained allowed to identify the obstetric profile of those women, breast complications such as cracked nipples, engorgement and mastitis. It is concluded that the Prenatal and Postpartum Nursing Consultation Project provided an opportunity to identify important breast complications, through health education in the postpartum period.